Synthesis and crystal structure of two-layer indotitanates Sr2LnInTiO7 - Titov, Y.A.; Belyavina, N.M.; Markiv, V.Ya.; Slobodyanik, M. S.; Polubinskii, V.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The extent of a region of compounds with layered perovskite-like structures (LPS) in the row of two-layer perovskites Sr2LnInTiO7 is determined. The new indotitanates Sr2LnInTiO7 (Ln – La, Pr, Nd, Sm) have been synthesized by heat treatment of equimolar mixtures Sr2TO4 + LnInO3, and their crystal LPS determined by X-ray powder diffraction. It is found that the LPS of Sr2LnInTiO7 (Ln – La, Pr, Nd, Sm) belongs to the BaLa2In2O7 – type structure (sp. gr. P42/mnm). The final RB values are equal to 0.060–0.069. The peculiarities of the two-layer LPS of Sr2LnInTiO7 are analyzed, and the composition – constitution correlations of the LPS have been identified.